Analisis Upaya Penyelesaian Nasabah Bank Wanprestasi Menurut Fatwa DSN MUI Nomor 4/DSN-MUI/IV/2000 - Nurkhozin (Indra Institute Research & Publication, 2024)
This study analyzes the efforts to resolve defaulting bank customers based on DSN MUI Fatwa No. 4/DSN-MUI/IV/2000. In the Islamic banking system, customers who default require approaches aligned with Sharia principles, such as negotiation, mediation, and arbitration. This study employs a qualitative method with a literature study approach to understand the provisions and implementation of the fatwa related to default resolution. The findings indicate that resolving defaulting customers in murabahah contracts involves restructuring, mediation, and Sharia arbitration in accordance with DSN MUI Fatwa provisions. Additionally, banks are obliged to provide guidance to customers in fulfilling their obligations while prioritizing justice and transparency. This study recommends optimizing the role of Islamic financial institutions in handling default cases more effectively and in compliance with Sharia principles.